Crescimento, fisiologia e produção da bananeira prata anã associada a plantas de cobertura e lâminas de irrigação. - Barbosa, Francisca Edineide Lima (2012)
The banana is of great importance in the national and world due to nutritional, social and especially economic. The use of techniques aimed at proper management of soil and water in this culture is of utmost importance for the development of sustainable agriculture, reducing environmental impacts. Given the above it is intended with this work, generate technological diffusion for the management of soil fertility, using legumes as a cover crop and irrigation in the cultivation of dwarf banana Prata (Musa spp.), Grown on Pentecoste - CE. The climate is semi-arid with erratic rainfall and the soil is classified as Neossolo Fluvic. The experimental design was a randomized block split plot with five replicates.The plots were formed by four irrigation levels: 50, 75, 100 and 125% of crop evapotranspiration (ETc) and the control subplots (conventional management without cover crops) and three types of cover crops intercropped with banana, They are: spontaneous vegetation (VE), tropical kudzu (Pueraria phaseoloides) in succession to crotalaria (Crotalaria juncea) (CK) and calopogônio (Calopogonium muconoides L) in succession to the bean-to-pig (Canavalia ensiformes) (FC). Legumes and beans sunn-of-pig were conducted before the transplanting of banana, and served as a mulch, while the tropical kudzu and calopogônio were planted one month after transplanting the banana and developed in a consortium and were managed as living roofs . In banana were evaluated: the number of leaves, height, pseudostem circumference, gas exchange, water use efficiency (U.S.), relative chlorophyll index (CRI), foliar macro and micronutrients and production. In the pre-planting legumes evaluated the biomass by fresh weight (MV) and shoot dry (MS) and evaluated in perennial legumes to MV, MS, CRI and contribution of N, exchanges gas and chlorophyll content. The witness provided plants with greater height and pseudostem circumference, higher leaf N content, lower cycle time and increased productivity followed by the consortium with calopogônio in succession to the bean-pork and kudzu in succession to crotalaria. The calopogônio responds to high radiation and seems to be more sensitive to shading and cutting, and kudzu most suitable for intercropping with banana plants, due to its excellent adaptation to shade imposed by the banana plantation.